2004
DOI: 10.1007/s00208-003-0497-7
|View full text |Cite
|
Sign up to set email alerts
|

Does polynomial parallel volume imply convexity?

Abstract: Abstract. For a non-empty compact set A ⊂ R d , d ≥ 2, and r ≥ 0, let A ⊕r denote the set of points whose distance from A is r at the most. It is well-known that the volume, V d (A ⊕r ), of A ⊕r is a polynomial of degree d in the parameter r if A is convex. We pursue the reverse question and ask whether A is necessarily convex if V d (A ⊕r ) is a polynomial in r. An affirmative answer is given in dimension d = 2, counterexamples are provided for d ≥ 3. A positive resolution of the question in all dimensions is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Note that in the two-dimensional special case of this result, which was first established in [8], the integration over the rotation group has no effect. Finally, Section 2 contains some geometric preparations which are needed for the proofs of our main results.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Note that in the two-dimensional special case of this result, which was first established in [8], the integration over the rotation group has no effect. Finally, Section 2 contains some geometric preparations which are needed for the proofs of our main results.…”
Section: Introductionsupporting
confidence: 52%
“…The aim of this subsection is to establish the following generalization of Theorem 1 in [8]. The result will be extended to higher dimensions and to random sets subsequently.…”
Section: The Two-dimensional Deterministic Casementioning
confidence: 92%
“…Heveling, Hug and Last [2] proved that a body in the Euclidean plane is convex, iff its parallel volume is a polynomial. This result was generalized by Hug, Last and Weil [3] to more general 2-dimensional Minkowski spaces and to random sets.…”
Section: Polynomial Parallel Volume and Convexitymentioning
confidence: 99%
“…This leads to a new proof of the following theorem by Heveling, Hug and Last [2]: Theorem 1.2. Let K ⊆ R 2 be a body, for which…”
Section: Introductionmentioning
confidence: 96%
“…Kneser [11] and Sz.-Nagy [18] obtained inequalities saying that the parallel volume of a fixed body considered as function of the distance cannot be "too convex". Heveling, Hug and Last [5] showed that a planar body can only have polynomial parallel volume if it is convex (see also [7]).…”
Section: Introductionmentioning
confidence: 99%